(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2024)
Atopic dermatitis in dogs is a chronic skin condition caused by allergies to environmental allergens such as pollen and dust mites. Symptoms include itching, inflammation and skin lesions. Diagnosis is based on clinical symptoms and exclusion of other diseases. Treatment includes environmental control measures, drug baths, immunomodulatory therapy and use of anti-inflammatory drugs. Prevention is done through appropriate environmental and food management. In this article, a case of atopic dermatitis will be reported in a male Shitzu dog treated at the Veterinary Hospital of the University of West São Paulo (UNOESTE), highlighting the importance of complementary exams and that dermatitis can be caused by certain natural foods. Also emphasizing the importance of effective therapy and proper assessment of clinical signs, enabling effective treatment significantly improving the quality of life of the animal, without, however, preventing the use of natural food